2005
DOI: 10.1159/000083297
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Occurrence of Amyotrophic Lateral Sclerosis among Gulf War (1990–1991) Veterans Using Capture-Recapture Methods

Abstract: Objective: Using data from a recent report that indicated a 2-fold higher risk of amyotrophic lateral sclerosis (ALS) among veterans of the 1991 Gulf War, we applied capture-recapture methodology to estimate possible under-ascertainment of ALS cases among deployed and non-deployed military personnel who were on active duty during that war. Study Design and Setting: One of the most serious concerns facing field epidemiological investigations is that of case ascertainment bias, particularly when it is differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 25 publications
0
47
0
1
Order By: Relevance
“…The proportion of unobserved cases in epidemiological studies on ALS has previously been estimated to be as high as 28% [14,20]. Not accounting for such an important bias is therefore likely to lead to a substantial underestimation of the true IR and PR [10,21]. In our study 10.3% of the incident and 14.0% of the prevalent cases from 2009 to 2011 were determined by the use of the capture-recapture method.…”
Section: Discussionmentioning
confidence: 90%
“…The proportion of unobserved cases in epidemiological studies on ALS has previously been estimated to be as high as 28% [14,20]. Not accounting for such an important bias is therefore likely to lead to a substantial underestimation of the true IR and PR [10,21]. In our study 10.3% of the incident and 14.0% of the prevalent cases from 2009 to 2011 were determined by the use of the capture-recapture method.…”
Section: Discussionmentioning
confidence: 90%
“…Specifically, the following types of sensitivity analyses will address the possibility of selection and survival bias: (1) we will restrict the analysis to cases (currently 76.4%) and controls (currently 82.4%) who applied for at least one VA benefit, since the BIRLS database captures all veterans from this group; this is essentially the subgroup of all US veterans who have made any contact with the Department of Veterans Affairs; (2) we will compare the exposure history of cases who were identified through active versus passive recruitment strategies; (3) in order to address the question of how completely the registry has identified all US veterans with ALS who were alive (prevalent cases) or newly diagnosed (incident cases) between April 2003 and September 2007, we will perform capture-recapture analyses similar to those performed for the Persian Gulf War study [93] ; (4) in order to address the possibility of survival bias, i.e. to distinguish exposure effects on ALS risk from effects on survival, we will restrict the analysis to incident cases; (5) a comparison of basic characteristics of the invited sample of potential controls, including those who could not be contacted or refused to participate, and the enrolled GENEVA controls ( tables 1 and 2 ) will help evaluate bias and indicate which variables are potentially important to adjust for in the analysis of exposure variables.…”
Section: Discussionmentioning
confidence: 99%
“…In both studies, veterans who were deployed to the Persian Gulf were approximately twice as likely to develop ALS as nondeployed veterans. Further analyses of data from one of these studies showed that this result was robust even after accounting for differential under-ascertainment between deployed and non-deployed individuals [19] . One study suggested an earlier age of onset for Persian Gulf War deployed veterans [18] .…”
Section: Introductionmentioning
confidence: 91%
“…1%, PLS: 6%). (98) 44 (2) 1,058 (98) 23 (2) 987 (98) (1) 1,030 (95) 29 (3) 4 (<1) 3 (<1) 15 (1) 907 (90) 82 (8) (2) 76 (4) 94 (4) 150 (7) 386 (18) 322 (15) 305 (15) 332 (16) 224 (11) 143 (7) 2 (<1) 24 (2) 44 (4) 47 (4) 87 (8) 214 (20) 186 (17) 164 (15) 167 (15) 96 (9) 50 (5) 10 (1) 21 (2) 32 (3) 47 (5) 63 (6) 172 (17) 137 (14) 141 (14) 165 (16) 128 (13) 92 (9) (19) 92 (6) 481 (29) 130 (7) 462 (28) 437 (21) 4 (<1) 328 (33) 165 (16) 34 (3) 224 (22) 63 (6) 201 (20) 214 (21) 6 (<1) 686 (33) 318 (19) 92 (6) 481 (29) 130 …”
Section: Color Codedunclassified